Gradient flows : in metric spaces and in the space of probability measures - Ambrosio, Luigi. (Springer, 2017)
Looking at the theory of gradient flows in spaces which are not necessarily endowed with a natural linear or differentiable structure, this text covers gradient flows in the space of probability measures on a separable Hilbert space, endowed with the Kantorovich-Rubinstein-Wasserstein distance and gradient flows in metric spaces.